(untitled) (Journal of Educational Sciences, 2018)
For many years foreign and native researchers have been making the attempts to discover the nature of giftedness. There are constant discussions whether giftedness is inherited or talent can be developed. The lack of unanimity on this issue has led to the development of numerous concepts of giftedness, which support different positions of the authors. There are different dimensions of such concepts, most widespread of which are psychological-pedagogical, philosophical and medical-biological. It is emphasized, that medical-biological dimension has not gained much attention yet. The aim of the article is to reveal the foreign medical-biological concepts of giftedness. In the article the following research methods are used: general – analysis, synthesis, comparison, classification and generalization, which are necessary for studying the works of foreign researchers; terminological analysis which helped reveal the essence of investigated pedagogical phenomena by detection and clarification of fundamental concepts. In the article a number of medical-biological concepts of giftedness have been characterized, in particular: “Model of the Dominant Hemisphere GBG”, “Concept of prenatal exposure and giftedness development”, “Prenatal exposures model of giftedness”. The highlighted models are aimed at explaining connection between the negative impacts during the processes of fetus development and emergence of either giftedness/different disorders or co-occurrence of giftedness and different disorders. Thus, medical-biological concepts of giftedness are based on the assumption that talent is conditioned by the unusual or unique development of the brain. These theoretical models not only provide understanding of emergence of giftedness from the neurophysiologic point of view, but also explain such phenomenon as “twice exceptionality”. It should also be stressed, that medical-biological concepts provide one of the ways of the solution of the problem on the nature of giftedness, while other aspects – psychological, philosophic, pedagogical etc. should also be considered in order to get versatile understanding of the studied phenomenon which will become the prospects for further research. Key words: giftedness, concepts of giftedness, medical-biological concepts of giftedness, nature of giftedness.